SKRINING PEMBENTUKAN BIOFILM PADA ISOLAT KLINIK STAPHYLOCOCCUS AUREUS PENYEBAB OMSK - , GEZA GETAR MI RAJ ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Chronic Suppurative Otitis Media (CSOM) is a chronic infection in the middle ear, followed by perforation of the tympani membrane with history of transparent or turbid discharged from ear for more than 2 months, constantly or intermittently. CSOM infection can reoccur despite having finished the treatment. Failure of therapy can happen because of the presence of biofilm formed by the bacteria that caused CSOM. One of the bacteria causing CSOM which has ability to form biofilm is Staphlococcus Aureus. Objective : Screening The Formation of Biofilm at Clinical Isolate of Staphylococcus Aureus as the cause of CSOM Method and material : This study used descriptive observational method. Qualtitative test of biofilm formation by the CRA method using Freeman scale and quantitative test by TCP method. Samples were obtained from the middle ear secretion of CSOM patient in the ENT clinic RSUP dr Sardjito from October-December 2012. Five clinical isolates Staphylococcus Aureus has obtained from these samples Results : From five clinical isolates, four isolates formed a biofilm and 1 isolate did not in the CRA method. While in the TCP method, all clinical isolate showed the ability to form biofilm (OD > 0,120)